Application of Potassium Ion Conducting KTiOPO4 as Effective Inner Solid-Contact Layer in All-Solid-State Potassium Ion-Selective Electrode. Issue 2 (15th February 2023) - Tatara, Ryoichi; Ishihara, Kenta; Kosugi, Motohiro; Aoki, Kazuma; Takei, Yuko; Matsui, Takahiro; Takayama, Toshiharu; Komaba, Shinichi
Abstract : Solid electrolytes used in all-solid-state batteries electronically separate the positive and negative electrodes in the battery and only allow the carrier ions to pass through. KTiOPO4 (KTP), a potassium ion-conducting solid electrolyte, was first applied as the inner solid contact layer of an all-solid-state potassium ion-selective electrode (ISE) to stabilize the membrane potential. Application of the KTP layer improved the long-term potential stability of the ISE by stabilizing the membrane potential. This can be further improved by adding acetylene black (AB) to the KTP layer which reduced the electrode resistance owing to its high double-layer capacitance.